2010
DOI: 10.1186/1471-2164-11-46
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metagenomic analysis of plasmid encoded functions in the human gut microbiome

Abstract: BackgroundLittle is known regarding the pool of mobile genetic elements associated with the human gut microbiome. In this study we employed the culture independent TRACA system to isolate novel plasmids from the human gut microbiota, and a comparative metagenomic analysis to investigate the distribution and relative abundance of functions encoded by these plasmids in the human gut microbiome.ResultsNovel plasmids were acquired from the human gut microbiome, and homologous nucleotide sequences with high identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(110 citation statements)
references
References 59 publications
(136 reference statements)
5
104
0
Order By: Relevance
“…While the relative abundance of plasmids or pollution-related accessory genes has been compared between polluted and clean control sites, no studies have so far compared gene contents of plasmids (64,(69)(70)(71)(72). The recently developed metagenomics approaches to assess the "plasmidome" or "metamobilome" (73,74) present one way to assess accessory gene content independent of what the plasmids encode, but obtaining reliable, closed genome sequences for large self-transmissible plasmids is still a challenge (75). Using the triparental mating approach, we showed the presence of diverse self-transmissible plasmids that do not carry known host-beneficial genes in natural environments.…”
Section: Discussionmentioning
confidence: 99%
“…While the relative abundance of plasmids or pollution-related accessory genes has been compared between polluted and clean control sites, no studies have so far compared gene contents of plasmids (64,(69)(70)(71)(72). The recently developed metagenomics approaches to assess the "plasmidome" or "metamobilome" (73,74) present one way to assess accessory gene content independent of what the plasmids encode, but obtaining reliable, closed genome sequences for large self-transmissible plasmids is still a challenge (75). Using the triparental mating approach, we showed the presence of diverse self-transmissible plasmids that do not carry known host-beneficial genes in natural environments.…”
Section: Discussionmentioning
confidence: 99%
“…The aph (2′′)-Ib gene was associated with mobile elements and was harboured by a strain from the genus Subdoligranulum that includes members of the group of anaerobic commensal microbiota. Our results suggested that these genetic mobile elements can be mobilized and/or have been acquired through horizontal gene transfer, as reported previously for members of the Firmicutes (Jones et al, 2010), which could contribute to the risk of transfer of antibiotic resistance genes from commensals to potential pathogens. It cannot be excluded that the increase of aminoglycoside resistance genes may also be an effect of the SDD therapy since tobramycin is used as part as the cocktail administrated to the patients.…”
Section: Antibiotic Therapy and The Human Gut Microbiotasupporting
confidence: 55%
“…This observation suggests that these resistance genes may be part of larger genetic elements that can be mobilised and/or which have been acquired through horizontal gene transfer. Evidence for the extensive transfer of antibiotic resistance genes in the gut microbiota has been observed before in Bacteroidetes and Firmicutes (Shoemaker et al, 2001;Jones et al, 2010). Consequently, the enrichment of antibiotic resistance genes in the patient's gut microbiota during SDD and their association with mobile genetic elements is a cause of concern as this may facilitate transfer of resistance genes to aerobic nosocomial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal microbiota (a term that has now replaced the old denomination of "microflora" [1,2]) is an ecosystem formed by a variety of ecological niches, made of several bacterial species and a very large amount of strains [3][4][5][6][7][8]. The microbiota is in close contact with the intestinal mucosa or epithelial interface which is, after the respiratory area, the largest surface of the body, occupying approximately 250-400 m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The human gut microbiota is currently the focus of very advanced research techniques -including studies on the bacterial genome (microbiome) -whose results are published in prestigious scientific journals [3][4][5][6][7][8]. Two major projects, based on systematic DNA sequencing of the microbiota, are currently in progress: (a) the Human Microbiome Project (HMP), in the USA and (b) the Metagenomics of the Human Intestine (metaHIT), held in Europe.…”
Section: Introductionmentioning
confidence: 99%